Protocolo de PCR para la detección de Brucella ovis - Alvarez, Lucia Paula; Robles, Carlos Alejandro (EEA Bariloche, INTA, 2020)
Adaptado de Xavier, M.N., Silva, T.M., Costa, E.A., Paixao, T.A., Moustacas, V.S., Carvalho, C.A., Jr., Sant'Anna, F.M., Robles, C.A., Gouveia, A.M., Lage, A.P., Tsolis, R.M., Santos, R.L., 2010. Development and evaluation of a species-specific PCR assay for the detection of Brucella ovis infection in rams. Vet Microbiol. 145, 158-164.